Cholecalciferol Supplementation Does Not Influence β-Cell Function and Insulin Action in Obese Adolescents: A Prospective Double-Blind Randomized Trial. Issue 2 (17th December 2014) - Javed, Asma; Vella, Adrian; Balagopal, P Babu; Fischer, Philip R; Weaver, Amy L; Piccinini, Francesca; Dalla Man, Chiara; Cobelli, Claudio; Giesler, Paula D; Laugen, Jeanette M; Kumar, Seema
Abstract: Background: There is increasing interest in the extraskeletal effects of vitamin D, particularly in the obese state with regard to the development of insulin resistance and diabetes. Objective: The objective of the study was to determine the effect of 2 doses of cholecalciferol (vitamin D3 ) supplementation on insulin action (Si ) and pancreatic β-cell function in obese adolescents. Methods: We performed a 12-wk double-blind, randomized comparison of the effect of vitamin D3 supplementation on Si and β-cell function in obese Caucasian adolescents (body mass index > 95 th percentile). The subjects were randomly assigned to receive either 400 IU/d ( n = 25) or 2000 IU/d ( n = 26) of vitamin D3 . Each subject underwent a 7-sample 75 g oral glucose tolerance test, with glucose, insulin, and C-peptide measurements, to calculate Si and β-cell function as assessed by the disposition index (DI), with use of the oral minimal model before and after supplementation. A total of 51 subjects aged 15.0 ± 1.9 y were enrolled. Included for analysis at follow-up were a total of 46 subjects (20 male and 26 female adolescents), 23 in each group. Results: Initial serum 25-hydroxyvitamin D [25(OH)D] was 24.0 ± 8.1 μg/L. There was no correlation between 25(OH)D concentrations and Si or DI. There was a modest but significant increase in 25(OH)D concentration in the 2000 IU/d group (3.1 ± 6.5 μg/L, P = 0.04) but not in the 400 IU/d group ( P = 0.39). There was no change in Si or DI following vitamin D3 supplementation in either of the treatment groups (all P > 0.10). Conclusions: The current study shows no effect from vitamin D3 supplementation, irrespective of its dose, on β-cell function or insulin action in obese nondiabetic adolescents with relatively good vitamin D status. Whether obese adolescents with vitamin D deficiency and impaired glucose metabolism would respond differently to vitamin D3 supplementation remains unclear and warrants further studies. This trial was registered atclinicaltrials.gov as NCT00858247.